2022
DOI: 10.1056/evidoa2100054
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Azithromycin Administration for Prevention of Infant Mortality

Abstract: Background. Biannual mass azithromycin administration reduces all-cause childhood mortality in some sub-Saharan African settings, with the largest effects in children aged 1-5 months. Azithromycin has not been distributed to children <1 month due to risk of infantile hypertrophic pyloric stenosis (IHPS).Methods. This 1:1 placebo-controlled trial, randomized neonates aged 8-27 days to a single oral dose of azithromycin (20 mg/kg) or equivalent volume of placebo in 5 regions of Burkina Faso during 2019 and 2020.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…The overall point estimate at 12 months of age (19% relative reduction in the azithromycin group) was similar to the point estimate from the trial's primary end point (15% relative reduction at 6 months of age), but the CIs were wide as a result of the low event rate. 3 As expected, causes of death were mostly infectious. Although the overall distribution of causes of death did not differ between arms, deaths determined to be the result of malaria were fewer in children randomized to azithromycin compared with placebo.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The overall point estimate at 12 months of age (19% relative reduction in the azithromycin group) was similar to the point estimate from the trial's primary end point (15% relative reduction at 6 months of age), but the CIs were wide as a result of the low event rate. 3 As expected, causes of death were mostly infectious. Although the overall distribution of causes of death did not differ between arms, deaths determined to be the result of malaria were fewer in children randomized to azithromycin compared with placebo.…”
Section: Discussionmentioning
confidence: 52%
“…The Data and Safety Monitoring Committee recommended continuation of the trial upon review of the interim analysis. 3 Study setting. Participants were enrolled in primary health-care facilities in five regions of Burkina Faso.…”
Section: Methodsmentioning
confidence: 99%
“…No cases of IHPS were reported in the MORDOR or CHAT trials. In addition, a recent individually randomised trial of azithromycin for neonates 8–27 days old was unable to demonstrate a difference in IHPS between neonates receiving azithromycin or placebo, as only a single case of IHPS was reported in the study population of 21 832 24. However, determining age in days accurately can be challenging in some settings that may receive these distributions.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, a recent individually randomised trial of azithromycin for neonates 8–27 days old was unable to demonstrate a difference in IHPS between neonates receiving azithromycin or placebo, as only a single case of IHPS was reported in the study population of 21 832. 24 However, determining age in days accurately can be challenging in some settings that may receive these distributions. Given these concerns, the main analyses presented here restricted the dosing for the youngest children to avoid dosing over 20 mg/kg and used more conservative tolerance limits than similar studies focused on older populations.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent review of the cost-effectiveness of community-based versus targeted azithromycin administration strategies for reducing child mortality in sub-Saharan Africa, it has been suggested that instead of MDA of azithromycin, targeting high-risk children is an option that could make economic sense while reducing exposure to azithromycin 28 , although the evidence supporting this strategy is currently limited. A trial in neonates receiving biannual azithromycin in sub-Saharan Africa found no evidence to support its' use for prevention of mortality 34 and a trial targeting children under 5 years after hospital discharge found no signi cant bene t of a 5-day course of azithromycin to the risk of death of rehospitalization 35 .…”
Section: Child Mortalitymentioning
confidence: 99%